2022
DOI: 10.15587/2519-4852.2022.253555
|View full text |Cite
|
Sign up to set email alerts
|

The analgesic and anti-inflammatory effect of lawsone isolated from Lawsonia inermis

Abstract: This study aimed to assess the analgesic and anti-inflammatory effects of lawsone isolated from henna leaves (Lawsonia inermis).  Methods: A total of 120 healthy adult mice (weighing about 25±5 g) were included in this study. Sixty mice out of the total were used to determine LD50, 30 mice to determine the anti-inflammatory test, and the remaining (30 mice) were used for an analgesic test. The hot plate was used to determine the analgesic effect, while the anti-inflammatory effect was determined by the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Its ease of application is associated with minimal pain and median cutaneous infiltration [33]. A research group evaluated the analgesic and anti-inflammatory effects of Lawsone isolated from Henna leaves (L. inermis) [31]. The results of this study unfolded that the bioactive molecule Lawsone induced a strong analgesic effect when compared to the positive control with aspirin and they concluded that Lawsone has analgesic and antiinflammatory effects, confirming the practical medical importance of the L. inermis species.…”
Section: Average Surface and Mean Percentage Of Burn Contractionmentioning
confidence: 80%
“…Its ease of application is associated with minimal pain and median cutaneous infiltration [33]. A research group evaluated the analgesic and anti-inflammatory effects of Lawsone isolated from Henna leaves (L. inermis) [31]. The results of this study unfolded that the bioactive molecule Lawsone induced a strong analgesic effect when compared to the positive control with aspirin and they concluded that Lawsone has analgesic and antiinflammatory effects, confirming the practical medical importance of the L. inermis species.…”
Section: Average Surface and Mean Percentage Of Burn Contractionmentioning
confidence: 80%
“…In addition, another trial demonstrated that a topical formulation of Henna resulted in a considerable improvement in contact dermatitis symptoms (22). These properties may be due to compounds derived from Henna, such as lawsone, isoplumbagin, and lawsaritol, which have anti-inflammatory and analgesic effects (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…However, lawsone had a stronger analgesic effect than aspirin. Lawsone and aspirin, on the other hand, had an anti-inflammatory effect in comparison to the control group and were equally effective in reducing carrageenan-induced hind paw edema (p = 0.05) (Ali et al, 2022).…”
Section: Biological and Pharmacological Effectsmentioning
confidence: 93%